Chad's crisis-prone transition: Dynastic consolidation and its risks - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2022)
Since President Idris Deby's violent death in April 2021, the ruling elite in Chad have sought to protect their hold on power by promoting the dynastic succession of his son Mahamat. The risks of this strategy are becoming clearer with the October 2022 decision to prolong the transition by another two years as Mahamat Deby is appointed interim president. With the emergence of new opposition forces, the tactic of dividing antagonistic elites through selective co-optation faces limits. Both in the capital and in the provinces, power struggles are fuelling identity-based mobilisation. The regime's repression of the opposition plays into the hands of the proponents of armed struggle. France, as the guarantor of Mahamat Deby's superior position vis-à-vis the rebels, is playing an increasingly unpopular role.
Keywords: 320; Chad; transition; Idris Deby; Mahamat Deby; Emmanuel Macron; European Union (EU); African Union (AU); National Dialogue; Front pour l'Alternance et la Concorde au Tchad (FACT); Conseil de Commandement Militaire pour le Salut de la République (CCMSR)